RADIONUCLIDE EVALUATION OF CONTRACTILITY OF THE RIGHT HEART IN MITRAL VALVE STENOSIS - K. V. Zavadovsky; A. V. Evtushenko; V. V. Saushkin; Yu. B. Lishmanov (Российский кардиологический журнал, 2015)
Aim. With the use of radionuclide weight-adjusted tomoventriculography (RTVG), to assess the condition of the right heart chambers in mitral valve stenosis (MV) of rheumatic origin.Material and methods. Totally, 20 patients studied (mean age — 54,2±8,22 y.) with rheumatic mitral valve lesion, of those 13 were investigated before and after correction of the defect. All patients, before and after correction of the defect were examined with the RTVG.Results. In all patients with the MV defect, we found a decrease of regional contractility of the RV. Patients with MV defects, related to the comparison group, had significantly more statistically decreased EF, MCI and SSN/Z, EF and higher values of EDV of the RV. Valve defect correction led to statistically more significant decrease of ESV, increase of MCI and EF RV. The sizes of the right atrium, measured with RTVG, were significantly higher comparing to the controls, and after correction of the defect, they reduced.Conclusion. The RTVG method could be applied for non-invasive assessment of the right heart chambers function in patients with MV stenosis of rheumatic origin.